A Tutor Agent for supporting distributed knowledge modelling in interactive product design. (25th February 2008) - Mejia-Gutierrez, Ricardo; Fischer, Xavier; Bennis, Fouad
Currently, the process of problem analysis in product design involves multiple partners in a distributed environment. A tutoring approach to support knowledge modelling will be presented in this article, focusing on variables as a key component of knowledge. A set of Tutor Agents intends to aid distributed partners to coherently elicitate their know-how in order to use to analyse design problems. A granular Knowledge Base is proposed to standardise distributed knowledge, providing Product Life-Cycle (PLC) constraints (based on product knowledge) to construct optimisation models. Furthermore, a case will be presented in order to clarify the approach. The results will enable design teams to integrate constraints from PLC knowledge in order to optimise the evolution of design concepts.